VARIATIONS IN SPORE AND SPORANGIUM SURFACE STRUCTURE OF THE FERN-ALLIES LYCOPODIACEAE P. BEAUV. EX MIRBEL IN MALAYSIA - Claysius Kongoi; Rusea Go; Runi Sylvester Pungga; Haja Maideen Kader (Tropical Life Sciences Research, 2007)
Thirty-two species, including eleven varieties from three genera of Lycopodiaceae found in Malaysia were examined for their spore’s wall morphology using scanning electron microscopy. Different genera showed different spore morphologies and distal face ornamentation. Foveolate and fossulate types of distal face ornamentation were the characteristics of the genus Huperzia, while the reticulate types were characteristic of the genus Lycopodium and the regulate type of the genus Lycopodiella. A preliminary study of the sporangium wall was also carried out in this study and is strongly taxonomically correlated. Tiga puluh dua spesies, termasuk sebelas variasi daripada tiga genera dari famili Lycopodiaceae dijumpai di Malaysia telah dikaji morfologi sporanya dengan menggunakan mikroskop imbasan elektron. Genera yang berbeza menunjukkan morfologi spora dan corak pada permukaan spora dari pandangan distal yang berbeza. Jenis foveolat dan fosulat merupakan ciri khas corak pada permukaan spora dari pandangan distal bagi genus Huperzia manakala jenis retikulat adalah ciri genus Lycopodium dan jenis rugulat genus Lycopodiella. Satu kajian awal dinding sporangium telah dijalankan dan ianya bererti dari segi taksonomi.